A Method for Measuring Fishing Effort by Small-scale Fish Aggregating Device (FAD) Fishers from the Commonwealth of Dominica. Issue 3 (August 2015) - Alvard, Michael; McGaffey, Ethan; Carlson, David
We used global positioning system (GPS) technology and tracking analysis to measure fishing effort by marine, small-scale, fish aggregating device (FAD) fishers of the Commonwealth of Dominica. FADs are human-made structures designed to float on the surface of the water and attract fish. They are also prone to common pool resource problems. To identify free riders with respect to specific FADs, we need to compare the cost expended for FAD construction versus the benefit fishers extract from their use of the FADs. From August to December 2012, we placed GPS devices on a sample of fishing trips to track movement and measure variation in fishers' fishing efforts at a set of seven FADs off the Atlantic east coast of central Dominica. The method produces high-resolution data to determine how much time different fishers use different FADs.